De-adoption and its 43 related terms: harmonizing low-value care terminology. Issue 1 (December 2015) - Gnjidic, Danijela; Elshaug, Adam
Abstract Research into the prevalence and impact of low-value medical practices has evolved substantially over the past two decades. However, despite international efforts, many challenges still remain with regards to progress in this field, including limits in the capacity to identify and prioritize low-value care practices and to systematically appraise clinical and policy attempts at redressing low-value care. A recent article by Niven et al. inBMC Medicine consolidates the current literature and terminology on the de-adoption of clinical practices, advocating the use of de-adoption as an appropriate term to label low-value care and proposes a new synthesis model to facilitate efforts to reverse ineffective and harmful medical practices. We hope that this work will facilitate advances in low-value care research and policy, and shift focus towards establishing evidence for de-adopting low-value interventions, which is crucial since attempts to reduce low-value care interventions have shown mixed results. Please see related article:http://www.biomedcentral.com/1741-7015/13/255